Sikap Peduli Lingkungan Peserta Didik di MAN-1 Pekanbaru Sebagai Sekolah Adiwiyata - Istiqomah Istiqomah (Dinamika Lingkungan Indonesia, 2019)
Current environmental problems continue to experience a serious increase. One way to reduce the threat of pollution is to change the outlook and attitudes of students to be more concerned about the environment. Adiwiyata school program is one way that can be followed to achieve these goals. This study aims to analyze the environmental attitudes of students in MAN-1 Pekanbaru who have held the status of Adiwiyata school since 2010. The research was conducted at MAN-1 Pekanbaru with a sample of 270 people using survey methods. The environmental care attitude questionnaire was compiled based on 5 indicators namely attitudes towards waste, attitudes towards energy indicators, attitudes towards water, land and air indicators, attitudes towards flora and fauna indicators and attitudes towards humans and the social environment. The results of the analysis show that the highest attitude indicator is on the attitude indicator towards humans and the social environment with an average value of 4.15, followed by an attitude indicator towards energy with an average of 3.97, an indicator of attitude towards waste of 3.79, an indicator of attitude towards air, air and land of 3.64 and indicators of attitudes towards flora and fauna of 3.57. While the environmental care category was dominated by the good category at 87.4%, the very good category at 10.37% and the low attitude category at 2.22%.